Normer, stigman och professionell samtalshjälp - En kvantitativ enkätstudie om unga vuxnas attityder mot att söka hjälp vid stress, nedstämdhet och/eller oro - Berg,Sara; Paulsson,Rebecka (2016)
The aim of this study was to examine attitudes towards mental health help-seeking among young adults. By using a quantitative method, handing out questionnaires to 145 young adults in upper secondary schools in Skåne, we asked questions about their perceived mental health and how normal or stigmatizing they regarded help-seeking in general. In scientific studies and governmental reports regarding young adults and mental health it is shown that mental health is getting worse and despite this, the number of young adults seeking help due to this matter does not increase. Researchers also observed that these attitudes differ depending on gender because of masculine and feminine stereotypes and norms that come with being a man or a woman. Since it would not be possible for us, in this thesis, to cover all factors that could influence the attitudes toward mental health help-seeking, we chose to look into those most common in previous studies. Factors influencing the attitudes, according to research, are for instance: fear of not being treated well by the professional, not believing that the help would make a change, wanting to solve the problem on their own and concerns about being stigmatized for not following the norms. The results of this study showed that the differences in attitudes toward mental health help-seeking according to gender was not that big and men and women also agreed in most answers about how normal or stigmatizing they thought of mental illness.
Keywords: attitudes; help-seeking; mental health; young adults; gender; stigma; norms